Executive Function and Academic Performance among Taiwanese Students in Higher Education: A Correlational Study - Hung, Shuan Ju (Proceedings of the International Conference on Education, 2020)
The purpose of this study was to investigate the associations between EF components (i.e., working memory and inhibition) and academic performance among Taiwanese students in higher education. Participants were 54 students from an educational psychology course at a private university in central Taiwan. Their EF was measured by the Adult Executive Functioning Inventory (ADEXI) and academic performance was measured by three scores: midterm exam score, final exam score and total score. Pearson’s correlational coefficient was computed to assess the correlations between EF components and academic performance in the current sample. Statistical significance for data analysis was set at p < .05. No significant correlations were found between the subscale of working memory and midterm scores (r = .045, p = .749), final exam scores (r = .129, p = .351) and total scores (r = .092, p = .509). Similarly, the associations of the subscale of inhibition with midterm scores (r = -.200, p = .148), final exam scores (r = -.225, p = .102) and total scores (r = -.222, p = .107) were not statistically pronounced. Although significant associations between the components of EF and academic performance in our sample were not observed, several explanations for the findings and implications for future research were provided.